2017
DOI: 10.1016/j.neuropsychologia.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Early processing of orthographic language membership information in bilingual visual word recognition: Evidence from ERPs

Abstract: For successful language comprehension, bilinguals often must exert top-down control to access and select lexical representations within a single language. These control processes may critically depend on identification of the language to which a word belongs, but it is currently unclear when different sources of such language membership information become available during word recognition. In the present study, we used event-related potentials to investigate the time course of influence of orthographic languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
(57 reference statements)
3
14
0
1
Order By: Relevance
“…400 pseudowords were created using Wuggy (Keuleers & Brysbaert, 2010), including 56 from Experiment 1. Pseudowords were matched pairwise to each critical word on length and orthographic bias (Hoversten et al, 2017) so that each set of translation pairs was paired with two pseudowords. This manipulation allowed us to test whether orthographic bias alone would drive skipping differences between non-switch and code switch conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…400 pseudowords were created using Wuggy (Keuleers & Brysbaert, 2010), including 56 from Experiment 1. Pseudowords were matched pairwise to each critical word on length and orthographic bias (Hoversten et al, 2017) so that each set of translation pairs was paired with two pseudowords. This manipulation allowed us to test whether orthographic bias alone would drive skipping differences between non-switch and code switch conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We then used the Wuggy software program (Keuleers & Brysbaert, 2010) to create 61 pseudowords that were pronounceable in either language and length-matched to the word pairs. These pseudowords did not resemble either language more strongly according to their mean bigram frequency in each language (see Hoversten et al, 2017 for further explanation of this measure).…”
Section: Stimulimentioning
confidence: 97%
See 1 more Smart Citation
“…The detection of orthotactic patterns is influenced by participants' sensitivity to statistical regularities within languages. So far, the evidence from previous studies suggests that language detection mechanisms are highly sensitive to violations of sub-lexical orthographic regularities of the native language [33][34][35]37,40,41,55], but not of the second language [37,38,40]. In other words, detecting L1 marked words is more difficult than detecting L2 marked words.…”
Section: Orthotactic Phonotactic and Feature Language Nodesmentioning
confidence: 99%
“…According to Wijers et al (1987), the higher visual load would make N1 amplitude more negative [33]. Hoversten et al (2011) focused on early visual processing of users and showed that early visual processing would be affected by low-priority perceptive attributes, and at low attention, high-density images would induce more negative N1 amplitude of users [34]. Therefore, it was speculated that the insignificance of N1 amplitude between high and low perceptual experiences in this experiment might be caused by the differences in the complexity of the interfaces.…”
Section: Discussionmentioning
confidence: 99%